Environmental science for dummies - Spooner, Alecia M. (Hoboken, NJ : J. Wiley & Sons, 2012)
Environmental science is a fascinating subject, but some students have a hard time grasping the interrelationships of the natural world and the role that humans play within the environment. Presented in a straightforward format, this guide gives you plain-English, easy-to-understand explanations of the concepts and material you'll encounter in your introductory-level course.
Includes index.
Keywords: Environmental sciences